Simultaneous Prediction of Cosolvent Influence on Reaction Equilibrium and Michaelis Constants of Enzyme-Catalyzed Ketone Reductions - Wangler, Anton (ACS Omega, 2019)
[Image: see text] Understanding and quantification of cosolvent influences on enzyme-catalyzed reactions are driven by a twofold interest. On the one hand, cosolvents can simulate the cellular environment for deeper understanding of in cellulo reaction conditions. On the other hand, cosolvents are applied in biotechnology to tune yield and kinetics of reactions. Further, cosolvents are even present inherently, for example, for reactions with cofactor regeneration or for enzymes that need cosolvents in a function of a stabilizer. As the experimental determination of yield and kinetics is costly and time consuming, this work aims at providing a thermodynamic predictive approach that might allow screening cosolvent influences on yield and Michaelis constants. Reactions investigated in this work are the reduction of butanone and 2-pentanone under the influence of 17 wt % of the cosolvent polyethylene glycol 6000, which is also often used as a crowder to simulate cellular environments. The considered reactions were catalyzed by a genetically modified alcohol dehydrogenase (ADH 270). Predictions of cosolvent influences are based on accounting for a cosolvent-induced change of molecular interactions among the reacting agents as well as between the reacting agents and the solvent. Such interactions were characterized by activity coefficients of the reacting agents that were predicted by means of electrolyte perturbed-chain statistical associating fluid theory. This allowed simultaneously predicting the cosolvent effects on yield and Michaelis constants for two-substrate reactions for the first time.